Testing antimicrobial peptides inhibiting protein synthesis in living E. coli and K. pneumoniae using bio-orthogonal non-canonical amino-acid tagging - de Pascale, Luigi; D’Amore, Agnese; Di Stasi, Adriana; Morici, Martino; Pacor, Sabrina; Tossi, Alessandro; Pham, Thuy Duong; Fabbretti, Attilio; Wilson, Daniel N.; Mardirossian, Mario; Scocchi, Marco (Frontiers in Microbiology, 2025)
IntroductionAntimicrobial peptides (AMPs) inhibit bacteria through diverse mechanisms of action. While many AMPs exert their effects by interacting with and damaging bacterial membranes, a growing subset has been shown to target intracellular processes, such as protein synthesis. In this study, we assessed the suitability of the bio-orthogonal non-canonical amino acid tagging (BONCAT) technique to investigate the mechanism of action on protein synthesis of proline-rich antimicrobial peptides (PrAMPs) in living Gram-negative bacteria.MethodsBy combining BONCAT with flow cytometry to evaluate membrane integrity using propidium iodide assay we first validated the effective inhibitory activity of PrAMPs on protein synthesis leaving intact the bacterial inner membrane in both Escherichia coli and Klebsiella pneumoniae, thus extending beyond E. coli as the sole model organism.ResultsWe demonstrated that this approach can discriminate between AMP affecting protein synthesis from those with membranolytic activity. We showed that different PrAMPs, significantly reduced the protein synthesis in 10 min, suggesting a very rapid inhibition kinetics. Furthermore, unlike chloramphenicol, PrAMPs demonstrated a prolonged inhibitory effect on protein synthesis even after the peptides were removed from the medium, suggesting a long-lasting post-antibiotic effect.DiscussionWe therefore demonstrated the validity of BONCAT as a tool for studying the molecular mechanisms of PrAMPs and we suggest that, in principle, this method may be extended also to other types of antimicrobial compounds to provide new insights into their mode of action on living bacteria.